Product-liability under contracts of sale and hire-purchase / Lailawati Husain - Husain, Lailawati (Faculty of Law, 1985)
Our present law on product liability is unsatisfactory. Improvement to our law e specially as regards to sale of goods and hire-purchase need to be modified. We have to take a view what is fair, and just and what proper balance should be maintained between the interest of the producers or manufacturers and consumers. Before going further in examining the law in this area it would be most proper to look at the meaning of the term "product liability". A. Defination of Product Liability The term product liability is not clearly defined by any statute. However an attempt to define the term was made by follows; Dodson as "The liability for injury or loss which may be imposed upon those persons who puts goods into circulation in a defective condition whether those persons be the. actual manufacturers or not".1 As there is no defination to be made as to "defective" in relation to the product, it is worth setting out the defination made by the Law Commission (United Kingdom) for the purpose of their recommendations.